Learning from the Past: Reflecting on the Maya-ICBG Controversy in the Classroom - Daniela Shebitz; Angela Oviedo (Ethnobiology Letters, 2018)
In the 1990s, the Maya-ICBG (International Cooperative Biodiversity Group) was one of the major bioprospecting projects in Chiapas, Mexico and was designed to incorporate traditional knowledge into pharmaceutical research. The researchers had hopes of benefiting Indigenous communities economically and technologically while conserving plants and traditional knowledge. Unfortunately, the project experienced local and international opposition who accused the project of exploiting Indigenous people and privatizing their knowledge. We present a teaching module in the form of an interrupted case study in which participants learn about the ethnobotanical study that shifted from one of promise to one of controversy. The history of the development of the case study over the past decade is told from both a faculty and a student perspective. The purpose of this perspective article and of our case study in general is to bring the conversation of ethics to the forefront of ethnobiology. Although the Maya-ICBG project was brought to a close in 2001, the case study is still relevant in both a historical context and as a means to discuss ethics and Prior Informed Consent.